2008
DOI: 10.1097/tp.0b013e318189064c
|View full text |Cite
|
Sign up to set email alerts
|

Response to Booster Hepatitis B Vaccines in Liver-Transplanted Children Primarily Vaccinated in Infancy

Abstract: Primary HBV vaccination or the booster dose(s) of HBV vaccine could provide adequate humoral and cellular immunity in children with LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
3
5
0
1
Order By: Relevance
“…In this previous study, long-term and repetitive vaccine stimulation was shown to be an important method with which to create and cultivate an enhanced immune response in these immunocompromised patients. Similar to this study, a few pediatric studies have reported the use of intermittent vaccination reinforcement, or booster vaccination, to maintain spontaneous anti-HBs production in children after liver transplantation[ 10 , 24 , 25 ]. For example, Ni[ 25 ] studied both the humoral and cellular immunity of booster hepatitis B vaccines in children after liver transplantation and demonstrated that the immunological response following a booster dose appeared to be adequate, at least over the short term (2 mo assessment period).…”
Section: Discussionsupporting
confidence: 58%
“…In this previous study, long-term and repetitive vaccine stimulation was shown to be an important method with which to create and cultivate an enhanced immune response in these immunocompromised patients. Similar to this study, a few pediatric studies have reported the use of intermittent vaccination reinforcement, or booster vaccination, to maintain spontaneous anti-HBs production in children after liver transplantation[ 10 , 24 , 25 ]. For example, Ni[ 25 ] studied both the humoral and cellular immunity of booster hepatitis B vaccines in children after liver transplantation and demonstrated that the immunological response following a booster dose appeared to be adequate, at least over the short term (2 mo assessment period).…”
Section: Discussionsupporting
confidence: 58%
“…Most trials applied a multi dose scheme. In adult SOT recipients, the response rate was low ranging from 6.7% to 36% while in contrast, a high response rate was seen in the paediatric trials ranging from 63.6% to 100% (Figure 2, category B) [29][31]. Overall, response rate to HBV after transplantation in adult SOT recipients is poor while in paediatric SOT recipients a 58% (95 CI: 37%–80%) higher response rate was seen (p = 0.001 from meta-regression).…”
Section: Resultsmentioning
confidence: 99%
“…We identified seven trials on hepatitis B vaccination after SOT with publication dates ranging from 1992 to 2001 (Table 3, category B) [25][31]. Six trials were prospective uncontrolled while one trial was retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-HBs antibodies can be reliably measured by standardised tests, but no standardised method is yet available for measuring specific immune memory. In studies in which immune memory was shown by means of the increase in anti-HBs after booster vaccination, anti-HBs titres were mostly measured only once and at rather different time points, ranging from 10 days to 2 months post-booster [7,[18][19][20][21]. In addition, in some studies anamnestic response was defined as an increase in anti-HBs to ≥10 IU/l [21][22][23][24][25], in other studies as 4-fold increase in anti-HBs [5], and sometimes both criteria were applied [13,15,20,26].…”
Section: Introductionmentioning
confidence: 99%